Hearing what matters: a case study of meaningful community engagement as a model to inform wellbeing initiatives - Miriam Sved; Ben Latham; Lyndsey Bateman; Libby Buckingham (Sax Institute, 2023)
Objectives: This paper contributes to the literature about community engagement processes that effectively support wellbeing approaches in government. Type of program or service: The Victorian Council of Social Service's Voices of Victoria Listening Tour ('the Tour') was a state-wide engagement with communities, and focused on people experiencing disadvantage. Delivered in partnership with Neighbourhood Houses Victoria and other community organisations, it sought to hear from lesser-heard voices about what people need for the foundational conditions of a good life. Methods: The Tour involved facilitated face-to-face sessions in community centres and targeted online sessions with underrepresented cohorts. Essential Media omnibus polling was conducted to test key findings with a wider participant group. Results: The Tour illuminated a variety of community needs and priorities, many of which overlap with the World Health Organization's social determinants of health. It revealed that people experiencing disadvantage often face problems that do not fall neatly into traditional government departments or portfolios. This shows the value of a whole-of-government wellbeing approach when addressing genuine community need. Structurally, the most productive elements of the community engagement process involved deliberate consideration of the specific conditions that put community members at their ease and empowered them to engage and participate. Lessons learnt: People experiencing disadvantage are rarely directly heard by policy makers. Designing and refining wellbeing approaches in partnership with diverse communities requires methods of engagement that are themselves contributors to community wellbeing. People are overwhelmingly appreciative of being listened to about what matters to them and of being active participants in decision making.